Optimizing cryoballoon pulmonary vein isolation: lessons from >1000 procedures— the Frankfurt approach. Issue 6 (17th January 2021) - Bordignon, Stefano; Chen, Shaojie; Bologna, Fabrizio; Thohoku, Shota; Urbanek, Lukas; Willems, Franziska; Zanchi, Simone; Bianchini, Lorenzo; Trolese, Luca; Konstantinou, Athanasios; Fuernkranz, Alexander; Schmidt, Boris; et al.
Abstract: Aims: Cryoballoon (CB) pulmonary vein isolation (PVI) is an accepted ablation strategy for rhythm control in atrial fibrillation (AF). We describe efficacy and safety in a high volume centre with a long experience in the use of the second-generation CB (CB2). Methods and results: Consecutive paroxysmal AF (PAF) or persistent AF (persAF) patients undergoing CB2-PVI were enrolled. Procedural data, efficacy, and safety issues were systematically collected. The 28 mm CB2 was used in combination with an inner lumen spiral catheter, a luminal oesophageal temperature (LET) probe was used with a cut-off of 15°C, the phrenic nerve (PN) monitored during septal PVs ablation. Freeze duration was mainly set at 240 s with a bonus application in case of delayed time-to-isolation (TTI > 75 s). A total of 1017 CB2 procedures were analysed (58% male, 66 ± 12 years old, 70% with PAF). 3964 PVs were identified, 99.8% PVs isolated using solely the 28 mm CB. Mean procedure time was 69 ± 25 min, TTI during the first application was recorded in 77% of PVs after a mean of 48 ± 31 s. We recorded 0.2% cardiac tamponade, 4.8% PN injury (1.6% of PN palsy), and 19% of LET < 15°C. Among 725 patients with follow-up data, 84% with PAF and 75% with persAF were in stable SR at 1 year. Shorter freezing duration and longer TTI were procedural predictors for recurrence. Conclusion: Cryoballoon procedures are fast and associated with a benign safety profile. Shorter TTI and longer freeze durations are associated with sinus rhythm during follow-up. Graphical Abstract: